From Arjuna’s Crisis to Self-Resilience: Psychological Capital in the Bhagavad Gita and Vedanta - Relin D. E.; Ni Kadek Surpi; Aditya Ansu (Life and Death: Journal of Eschatology, 2026)
Background: Rapid social change, professional pressure, moral conflict, and existential uncertainty have increased the importance of psychological resources that enable individuals to remain purposeful and resilient during crises. Psychological capital, commonly formulated through hope, self-efficacy, optimism, and resilience, provides a useful framework for examining these resources; however, its dominant orientation toward individual performance and adaptation does not fully address the ethical, metaphysical, and spiritual foundations of human strength. This study aims to analyze Arjuna’s transformation from psychological and moral crisis to inner resilience in the Bhagavad Gita and to reconstruct psychological capital through the perspective of Vedanta. Methods: This study employed a qualitative textual-interpretive design combining directed qualitative content analysis and hermeneutic inquiry. The primary data consisted of selected passages from Chapters I, II, III, VI, XII, XIV, and XVIII of the Bhagavad Gita, particularly those depicting Arjuna’s crisis, Kṛṣṇa’s teachings, and Arjuna’s eventual restoration of clarity and agency. The data were coded deductively according to the four dimensions of psychological capital and inductively through Vedantic concepts, including ātman, dharma, buddhi, karma-yoga, samatva, abhyāsa, and vairāgya. Interpretations were subsequently compared with contemporary literature on psychological capital, resilience, Hindu psychology, and psychotherapy. Findings: Arjuna’s crisis represents a simultaneous collapse of hope, self-efficacy, optimism, and resilience caused by moral disorientation, identity fragmentation, emotional dysregulation, and the loss of a meaningful basis for action. Kṛṣṇa’s teachings reconstruct hope as a dharma-based normative orientation, self-efficacy as ethically disciplined agency directed by buddhi, optimism as non-illusory confidence in the intrinsic value of right action, and resilience as a transformative capacity grounded in samatva and non-attachment to outcomes. These dimensions are integrated in a circular process moving from value conflict and identity fragmentation toward clarification of the self, restoration of dharmic purpose, regulation of the mind, detached action, inner balance, and transformative resilience. Conclusion: The Bhagavad Gita expands psychological capital beyond adaptive performance by grounding psychological strength in ethical responsibility, spiritual awareness, and transformation of consciousness. Arjuna’s recovery demonstrates that resilience is not merely a return to previous functioning but the formation of a more integrated, reflective, and morally responsible mode of action. Novelty/Originality of this article: This study introduces the concepts of ethical-spiritual psychological capital and transformative resilience by systematically reconstructing the four dimensions of psychological capital through Vedantic categories rather than merely identifying parallels between the Bhagavad Gita and modern psychotherapy.